(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mining is second largest industry after agriculture at all scales and regions and it has played a vital role in the development of Civilization from ancient time. Most of the valuable material like metal, chemicals, fuel for energy, rocks and stones for building, all comes from mining. Mining is very long and complex process and involves several steps between the sampling and excavation of mineral ore to concentration and processing of the final products, leading to a variety into land degradation, followed by the continuing air, noise and water pollution till the final product is available.Kund slate mining area is located about 25 km. in the west of Rewari at Rewari-Narnaul State Highway. It lies between 28°7’30”-28°12’30”N latitudes and 76°20’-76°26’E longitudes in the survey of India toposheet no, 53 D8. The area is represented by moderate to steep high hills of slate and shaly Formation with an average elevation of about 40 metres from ground level. The contours of the area are distributed from 290-350m.The regional geology of the area is represented by different types of formation belonging to Delhi Super group. The slate of the area is exposed in the form of hillocks shows a general Strike trend of N 10° E to N 20° E with moderate to steep dips of 50° to 80° towards N80° to N70° W. The slate reserve of the area is found in the form of vein extended North to South about 8 km. long and 300 meter wide.The unplanned, unscientific and ruthless mining activity of slate stone has degraded more than 2400 hect. of land ( Forest and Agriculture Land ) in the form of mining and dumping overburdenmining waste. Besides this decline in biodiversity air, noise and water pollution, scarcity of animal fodder, lowering of ground water level are the most obvious effects of Kund slate mining area.